2003
DOI: 10.4088/jcp.v64n0916
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation and Attempts Among Psychiatric Patients With Major Depressive Disorder

Abstract: 9Abbreviations 11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
233
6
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(276 citation statements)
references
References 275 publications
(299 reference statements)
27
233
6
10
Order By: Relevance
“…Rather, these studies found that the relationship is mediated by suicidal ideation. That is, suicidal ideation is influenced by level of hopelessness and suicidal ideation influences risk of suicide attempt (Valtonen et al, 2005;Sokero et al, 2003;Dieserud et al, 2001). However, it is important to note that literature in this area has been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, these studies found that the relationship is mediated by suicidal ideation. That is, suicidal ideation is influenced by level of hopelessness and suicidal ideation influences risk of suicide attempt (Valtonen et al, 2005;Sokero et al, 2003;Dieserud et al, 2001). However, it is important to note that literature in this area has been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Each item is rated on a 3-point scale from 0 to 2; the higher the total score, the greater the severity of suicide ideation. In some previous studies on adult suicidality a score of 6 or more has been used as a cutoff threshold for clinically significant suicidal ideation (Sokero et al, 2003). While the 19-item SSI (Beck et al, 1979) was used to evaluate the current intensity of the patients' specific attitudes, behaviors, and plans to commit suicide, the first 5 items are used to screen for attitudes toward living and dying, and only patients who report a desire to make an active (item no.…”
Section: Scale For Suicide Ideation (Ssi)mentioning
confidence: 99%
“…Farmer et a1 12 found that 66% of people with MDD experienced SI in the previous week. In a population of psychiatric patients with MDD, Sokero et al 5 found that 58% experienced SI during the current MDE, and 95% of MDD patients who had attempted suicide had SI.…”
Section: S Erious Si Is Not Uncommon In the General Populationmentioning
confidence: 99%
“…Studies have consistently identified an association between SI and hopelessness. 5,[25][26][27] Patients with anxiety disorders have been shown to be at increased risk of SI. 17 In particular, studies have found SI to have a significant association with panic disorder.…”
Section: S Erious Si Is Not Uncommon In the General Populationmentioning
confidence: 99%
See 1 more Smart Citation